Peranan Komite dan Kepemimpinan Kepala Sekolah Serta Implementasinya dalam Manajemen Berbasis Sekolah - Muhammad Ihsan Dacholfany; Anak Agung Oka; Iswati (Al-Ulum, 2022)
This article focuses on the role of school principals and committees in implementing school-based management. This quantitative research uses an ex post facto approach. The population in this study were teachers at Muhammadiyah Vocational Schools throughout Metro City, totaling 70 teachers as the sample. Findings in this article The study results show a positive influence between the Leadership of the school principal and the school committee's role in implementing school-based management in Muhammadiyah Vocational Schools in Metro Lampung City, which is equal to 33.9 %. This is based on the calculation of the regression equation, which illustrates that the simultaneous increase in the school principal's leadership score and the school committee role score tends to be followed by an increase in the school-based management implementation score so that quantitatively if the two independent variables are linked together to the dependent variable, then the principal's Leadership contributes 0.4 84. The role of the school committee contributes 0.212 to the implementation of school-based management in a positive direction with a constant of 2 9.408.